(untitled) (Transport systems and technologies, 2018)
The article reviewed and tested principles of constructing a model of induction motor 92-4 AE-used for electric locomotives VL-80K, T as motor – fan in the windings asymmetry and non-sinusoidal voltage. The choice of the mathematical model by which described the motor – fan in these modes, designed and built the parameters of the model in the software environment Simulink software package MATHLab. Built transition curves for electricity and for the moment maпgnetic shaft speed induction motor, in which the tested model motor – fan on adequacy. The above simulation about the possibility of further auxiliary equipment (Phase separator, motor – compressor and motor – pump) to study these modes of asynchronous motors on overall power factor of electric drive auxiliary machinery series VL80T, K and develop methods to improve power factor. As a basic model of an induction motor, a motor-fan model will be used.